Sexual abuse victimisation and perpetration in a cohort of men living with HIV/AIDS who have sex with women from São Paulo, Brazil - Segurado, A. C.; Batistella, É; Nascimento, V.; Braga, P. E.; Filipe, E.; Santos, N.; Paiva, V. (Taylor & Francis, 2008)
Sexual abuse leads to physical harm and devastating psychosocial consequences. It increases risk of HIV transmission and is associated with risky behaviour. Little is known about sexual abuse victimisation (SAV) and perpetration (SAP) among HIV-positive men who have sex with women (MSW). We investigated self-reported SAV and SAP among 242 Brazilian MSW selected at HIV care centres. Patients were questioned about sociodemographic data, mode of HIV acquisition, sexual practices, drug use and history of SAV or SAP. Prevalence of outcomes was estimated and risk factors for SAP investigated by logistic regression. Fifty-eight (24.1%) interviewees reported SAV. Of patients abused before 15 years of age, 64.3% reported events before the age of ten. Aggressors included relatives, friends and teachers. Among those victimised after 15 years old, 57.7% described events before 17 and 38.5% had acquainted aggressors. Fourteen (5.8%) interviewees reported SAP and most knew their victims. Sexual abuse perpetration was associated with lower schooling, marital status, illicit drug use and self-reported SAV. Sexual abuse was frequently reported by MSW from this cohort. Identifying predictors of violence and addressing SAV and SAP in comprehensive HIV care may help reduce violent behaviour, psychological distress and contribute to maximise benefits of preventive and care interventions. © 2008 Taylor & Francis.